On the Synthesis, Characterization and Reactivity of N‐Heteroaryl–Boryl Radicals, a New Radical Class Based on Five‐Membered Ring Ligands. Issue 17 (13th March 2014) - Tehfe, Mohamad‐Ali; Schweizer, Stéphane; Chany, Anne‐Caroline; Ysacco, Cédric; Clément, Jean‐Louis; Gigmes, Didier; Morlet‐Savary, Fabrice; Fouassier, Jean‐Pierre; Neuburger, Markus; Tschamber, Théophile; Blanchard, Nicolas; Lalevée, Jacques
Abstract The synthesis and physical characterization of a new class of N‐heterocycle–boryl radicals is presented, based on five membered ring ligands with a N(sp2) complexation site. These pyrazole–boranes and pyrazaboles exhibit a low bond dissociation energy (BDE; BH) and accordingly excellent hydrogen transfer properties. Most importantly, a high modulation of the BDE(BH) by the fine tuning of the N‐heterocyclic ligand was obtained in this series and could be correlated with the spin density on the boron atom of the corresponding radical. The reactivity of the latter for small molecule chemistry has been studied through the determination of several reaction rate constants corresponding to addition to alkenes and alkynes, addition to O2, oxidation by iodonium salts and halogen abstraction from alkyl halides. Two selected applications of N‐heterocycle–boryl radicals are also proposed herein, for radical polymerization and for radical dehalogenation reactions.